Multiphoton luminescence imaging of chemically functionalized multi-walled carbon nanotubes in cells and solid tumors1. Issue 45 (7th June 2015) - Rubio, N.; Hirvonen, L. M.; Chong, E. Z.; Wang, J. T. W.; Bourgognon, M.; Kafa, H.; Hassan, H. A. F. M.; Al-Jamal, W. T.; McCarthy, D.; Hogstrand, C.; Festy, F.; Al-Jamal, K. T.
<x xml:space="preserve">Abstract</x> A simplified scheme showing the non-linear photoluminescence properties of f-MWNTs and their potential use as imaging tools in cells and tumors.